Government Finance Statistics Manual, 2001. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Manual, which updates the first edition published in 1986, is a major advance in the standards for compilation and presentation of fiscal statistics. It is intended as a reference volume for compilers of government finance statistics, fiscal analysts, and other users of fiscal data. The Manual introduces accrual accounting, balance sheets, and complete coverage of government economic and financial activities. It covers concepts, definitions, classifications, and accounting rules, and provides a comprehensive framework for analysis, planning, and policy determination. To the extent possible, the Manual has been harmonized with the System of National Accounts 1993.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet